Pengaruh Pemberian Sari Buah Salak (Salacca zalacca) terhadap Profil lipid dan Berat Badan Tikus Model Hiperlipidemia dan Obesitasda - Datu, Olvie Syenni; Lebang, Julianri Sari; Rumondor, Erladys Melindah (Sam Ratulangi University, 2022)
Cardiovaskular disease is the number one cause of death in the world, an estimated 17.9 million people die each year. Several risk factors that contribute to the occurrence of heart disease such as hypertension, diabetes mellitus, hyperlipidemia, and obesity. Snake Fruit is a fruit that is available in large quantities both in volume and variety. Snake Fruit is rich in antioxidants that can be used to treat hyperlipidemia and overweight. North Sulawesi is one of the centers of Snake Fruit production, especially in the southeast Minahasa area. This study aimed to test the effectiveness of Snake Fruit juice on the lipid profile of hyperlipidemic and obese rats induced by a high-fat diet in the form of used cooking oil, quail egg yolk and 0.01% PTU solution. The study used 5 groups, namely the negative control group was given aquadest, the positive control group was given simvastatin and the treatment group was given Snake Fruit juice with concentrations of 2%, 4% and 8%. The parameters observed in this study were body weight, lipid profile, and glucose profile. blood. The study showed that the administration of Snake Fruit juice had a significant effect on the lipid profile of rats for all parameters on the lipid profile and had a significant effect on weight loss and blood glucose levels where p < 0.05 and there was no significant difference between each treatment group in both lipid profile parameters. , body weight and blood glucose levels.